Novel coronavirus infection in children outside of Wuhan, China - Shen, Qinxue; Guo, Wei; Guo, Ting; Li, Jinhua; He, Wenlong; Ni, Shanshan; Ouyang, Xiaoli; Liu, Jiyang; Xie, Yuanlin; Tan, Xin; Zhou, Zhiguo; Peng, Hong (Pediatric pulmonology, 2020)
Background Since December 8, 2019, an epidemic of coronavirus disease 2019 (COVID‐19) has spread rapidly, but information about children with COVID‐19 is limited. Methods This retrospective and the single‐center study were done at the Public Health Clinic Center of Changsha, Hunan, China. We identified all hospitalized children diagnosed with COVID‐19 between January 8, 2019 and February 19, 2020, in Changsha. Epidemiological and clinical data of these children were collected and analyzed. Outcomes were followed until February 26th, 2020. Results By February 19, 2020, nine pediatric patients were identified as having 2019‐nCoV infection in Changsha. Six children had a family exposure and could provide the exact dates of close contact with someone who was confirmed to have 2019‐nCoV infection, among whom the median incubation period was 7.5 days. The initial symptoms of the nine children were mild, including fever (3/9), diarrhea (2/9), cough (1/9), and sore throat (1/9), two had no symptoms. Two of the enrolled patients showed small ground‐glass opacity of chest computed tomography scan. As of February 26, six patients had a negative RT‐PCR for 2019‐nCoV and were discharged. The median time from exposure to a negative RT‐PCR was 14 days. Conclusions The clinical symptoms of the new coronavirus infection in children were not typical and showed a less aggressive clinical course than teenage and adult patients. Children who have a familial clustering or have a family member with a definite diagnosis should be reported to ensure a timely diagnosis.